Strengthening the Science-Policy Interface: Collaborating with Kenya's Stakeholders and Policymakers to Inform Agricultural Policy Formulation and Operationalize Recommendations from the 1st Kenya Food Systems Conference - Kirui, Leonard; Maru, Joyce; Saika, Sheewa (CGIAR System Organization, 2023)
The policy engagement workshop held in Naivasha from 2nd to 4th May 2023, organized by the CGIAR Initiative on National Policies and Strategies (NPS) and Kenya’s Ministry of Agriculture and Livestock Development (MoALD), brought together stakeholders and policymakers with the aim of integrating recommendations from the 1st Kenya Food Systems Conference (KFSC) into national policy frameworks. This collaborative effort is geared towards informing agricultural policy formulation and operationalizing those recommendations, focusing on six key areas: Cross-cutting issues, health, productivity, resilience, inclusion, and sustainability.